Analysis Validity, Readability, and Practicality of the Ecosystem E-Booklet Based on the Local Potential of Grogolan Spring to Improve Students’ Critical Thinking Ability - Nur Rohmah Tria Romadhoni; Alimah, Siti; Ellianawati, Ellianawati (Universitas Negeri Semarang, 2024)
This study aims to analyze the validity, readability, and practicallity of e-booklet on ecosystem material based on the local potential of the Grogolan spring in Bojonegoro which can improve students’ critical thinking skills through contextual learning. Contextual learning is considered important as it allows students to learn in a real-world context and experience firsthand what they are learning, rather than just reading and memorizing material. The local potential-based e-booklet is expected to make the material more meaningful and relevant to students, thereby improving their critical thinking skills. The subject of the study was a grade X student at Tambakrejo High School. Data analysis included the validity, readability, and practicality of the e-booklet. The research results showed that (1) The e-booklet contain specific information about ecosystem materials that utilize the local potential of Grogolan Spring in Bojonegoro, which is used as a learning resource. (2) The validity of the e-booklet, based on expert assessments, obtained an average score of 95.4% for material assessment and 93% for media assessment, both categorized as very valid, the small-scale readability test by teachers obtained an average score of 94.5% and by students an average score of 88.3%, both in the very good category. (3) The practicality assessment of using the local potential-based e-booklet obtained a score of 95.5% by teachers and 84.3% by students, both showing very practical categories. Based on the researach, it can be concluded that the local potential-based e-booklet is declared feasible, potentially to improve the critical thinking skills of high school learners.